Multispectral analysis of high spatial resolution 256-channel radiometrics for soil and regolith mapping - Beckett, Kirsty A (Curtin University, 2007)
Over the past decade studies into the application of radiometrics for soil and regolith mapping have met with mixed response. While the use of radiometric data for regolith mapping has been generally well received, radiometric methods have not commonly been adopted to assist and improve soil mapping. This thesis contributes to the development of radiometric techniques as soil and regolith mapping tools by examining soil characteristics and radiometric response using non-standard radiometric methods. This is accomplished through the development of new data processing methodologies, which extracts additional information from standard radiometric data that is unattainable using standard processing methods, and development of a new interpretation approach to soil and regolith mapping employing the multispectral processed radiometric data. The new multispectral processing methodology resolves seven gamma ray peaks from standard 256-channel NaI radiometric data to produce new radiometric uranium ternary, thorium ternary and uranium ratio imagery. Changes in the gamma ray relationships, identified through the new imagery, identify changes in soil and/or environmental conditions that are absent or difficult to identify in the standard radiometric imagery. With the isolation of non-standard thorium channels 228 [superscript] Ac (900 keV) and 228 [superscript] Ac (1600 keV), case studies in this thesis demonstrate how the difference of 1.9 years (half-life) between thorium 228 [superscript] Ac and 232 [superscript] Th decay daughter products can be mapped through the interpretation of thorium energy using ternary imagery [red: 208 [superscript] Tl (1764 keV), green: 228 [superscript] Ac (900 keV), blue: 228 [superscript] Ac (1600 keV)]. Energy peak differences may be be linked to local variations in soil chemistry, soil movement, and water movement.Additionally, through the isolation of non-standard uranium channels 214 [superscript] Bi (1120 keV) and 214 [superscript] Bi (1253 keV), preferential attenuation of lower energy gamma-rays from 214 [superscript] Bi decay events are exploited to map variations in soil density and/or porosity. These variations are illustrated through the interpretation of uranium energy using ternary imagery [red: 214 [superscript] Bi (1764 keV), green: 214 [superscript] Bi (1120 keV), blue: 214 [superscript] Bi (1253 keV)] and uranium peak energy ratio [214 [superscript] Bi 1120 keV / 214 [superscript] Bi 1764 keV] pseudo colour imagery. Case studies examined in this thesis explore the characteristics of 256-channel radiometric spectrum from different resolution datasets from different Western Australian soil types, provide recommendations for acquiring radiometric data for soil mapping in different agricultural environments, demonstrate how high resolution 256-channel radiometric data can be used to model soil properties in three-dimensions, and illustrate how three-dimension soil models can be used to separate surface waterlogging influences from rising groundwater induced waterlogging.